2015
DOI: 10.5430/ijhe.v5n1p11
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Socio-Demographics and Stress Levels, Stressors, and Coping Mechanisms among Undergraduate Students at a University in Barbados

Abstract: This study sought to learn about stress experienced by students enrolled in the Faculty of Social Sciences (FSS) at the University of the West Indies (UWI) in Barbados. This research was primarily undertaken to help UWI administrators/academic staff understand and address student stress. One hundred and six FSS students responded to:-(1) student perceptions on whether summer school courses were less stressful compared to semester courses, (2) the mean stress level associated with summer and semester courses, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
4
0
3
Order By: Relevance
“…Religiosity is still an interesting subject for researchers, with some academic studies getting associated with religiosity and student religiosity commitment [1,2] In much of the literature, religiosity and spirituality are two interchangeable terms [3] Several studies have shown the significant influence of religiosity and spirituality on individual's existence [4] including life pattern, behavior, and work, while possessing a substantial gap regarding the relationship between religiosity and spirituality with performance. Religious beliefs have the ability to make significant differences on individual behavior and performance, by providing a frame of reference in making decisions, especially in both multi-cultural and multi-religious environments [4] Despite their extensive use in research, religiosity and spirituality do not have a universally accepted definition [5] Religiosity and spirituality are not the same phenomenon, even though most people agree that the two are constructively related [6] Further in this study the two constructs are independent, with religiosity being a religious zeal as adopted by McGregor et al [7] Meanwhile, spirituality is an individual's perception of beliefs, intuition, lifestyle choices, practices, and rituals, which are all considered as spiritual condition as adopted by Delaney [8] Furthermore, although still a debate, the relationship between religiosity, spirituality, academic motivation and performance has been confirmed. The relationship between religiosity and academic motivation has been supported by many researchers [9,10,1,11,12] In addition, religiosity has also been discovered to be related to and influence students' performance ([13-16] However, several other researchers discovered no relationship between religiosity and academic performance [17,1,18].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Religiosity is still an interesting subject for researchers, with some academic studies getting associated with religiosity and student religiosity commitment [1,2] In much of the literature, religiosity and spirituality are two interchangeable terms [3] Several studies have shown the significant influence of religiosity and spirituality on individual's existence [4] including life pattern, behavior, and work, while possessing a substantial gap regarding the relationship between religiosity and spirituality with performance. Religious beliefs have the ability to make significant differences on individual behavior and performance, by providing a frame of reference in making decisions, especially in both multi-cultural and multi-religious environments [4] Despite their extensive use in research, religiosity and spirituality do not have a universally accepted definition [5] Religiosity and spirituality are not the same phenomenon, even though most people agree that the two are constructively related [6] Further in this study the two constructs are independent, with religiosity being a religious zeal as adopted by McGregor et al [7] Meanwhile, spirituality is an individual's perception of beliefs, intuition, lifestyle choices, practices, and rituals, which are all considered as spiritual condition as adopted by Delaney [8] Furthermore, although still a debate, the relationship between religiosity, spirituality, academic motivation and performance has been confirmed. The relationship between religiosity and academic motivation has been supported by many researchers [9,10,1,11,12] In addition, religiosity has also been discovered to be related to and influence students' performance ([13-16] However, several other researchers discovered no relationship between religiosity and academic performance [17,1,18].…”
Section: Introductionmentioning
confidence: 82%
“…IM and EM), and students' performance which were adopted from previous studies. The religiosity questionnaire was adopted from McGregor et al [7] (e.g., "I am confident in my religious beliefs", α = 0.893). Spirituality constructs were measured using questionnaires from Delaney [8] (e.g., "I find meaning in my life experiences", α = 0.883).…”
Section: Measurement Scalesmentioning
confidence: 99%
“…Admission to a university programme constitutes a relevant step for a student insofar as it entails the beginning of the professional training process. However, despite being motivated to pursue a degree, a student may find it difficult to adapt to this new environment due to demands related to the requirements of the course of studies, the institution, interpersonal relationships, and emotional aspects such as stress and anxiety (Moreno & Soares, 2014 ; Persaud & Persaud, 2016 ). The academic path involves many obstacles and stress-generating situations that can negatively impact academic success and the student’s adaptation to university life (Mthimunye & Daniels, 2019 ).…”
mentioning
confidence: 99%
“…Estudos com alunos sem deficiência (Lameu et al, 2016;Moreira & Furegato, 2013;Persaud & Persaud, 2015e Santos et al, 2012 que tiveram por objetivo detectar os aspectos do ambiente acadêmico que geram estresse concluíram que as demandas acadêmicas aumentam os níveis de estresse e que as universidades devem proporcionar programas com ações preventivas e terapêuticas a fim de garantir o bem estar desse público. Os resultados desses estudos vão ao encontro de pesquisas realizadas com estudantes com deficiência no Ensino Superior.…”
Section: Estresseunclassified